Predicting Consumers’ Purchase Intentions for Sex Toys : An Application of the Theory of Planned Behavior - Järvinen, Elina (fi=Turun yliopisto|en=University of Turku|, 2017)
The sex toy market has been in a turmoil for the last decades. The more liberal attitudes towards sex-related issues and the possibility to buy sex toys anonymously online, have contributed to the growth of the sex toy industry. The purpose of the thesis was to investigate factors that predict consumer purchase intentions for sex toys using the theory of planned behavior as a theoretical framework. The following research questions were presented: What are the beliefs that consumers have about purchasing sex toys? To what extent do attitude, subjective norm, perceived behavior control, and past purchase behavior predict purchase intentions for sex toys? How do high purchase intention and low purchase intention groups vary according to demographic characteristics? A sequential mixed methods research design was adopted for the empirical part of this study. The qualitative research included expert interviews and a belief elicitation study. Expert interviews (N=2) were conducted in order to better understand the phenomenon. A belief elicitation study (N=42) was conducted to find out the salient beliefs of the consumers regarding the purchasing of sex toys. For the quantitative part of the study, the findings from the qualitative research were applied to form a survey questionnaire. An online survey, with a nationally representative random sample (N=521) of respondents aged 18–65 years, was conducted in Finnish in Webropol. Three factors: playfulness, sexual health, and relationship maintenance were extracted for attitude construct. Five factors: knowledge, privacy, location, embarrassment, and ethics were extracted for perceived behavioral control in an exploratory factor analysis. Confirmatory factor analysis confirmed the measurement model for both constructs. The measure for subjective norm was constructed from the influence of partner, healthcare professionals, and friends. A sequential regression analysis was conducted for two separate models. Both models explained 55% of purchase intentions. Attitude and past purchase behavior were found to be the best predictors for purchase intentions. Subjective norm and perceived behavioral control had little or no effect on purchase intentions. Low purchase intentions were expressed by 21% of the respondents and high purchase intentions by 58%. χ2-test revealed no significant differences in high and low purchase intention groups against demographic variables. According to the findings attitude towards the purchasing of sex toys was positively affected by beliefs about sex toys bringing playfulness to sex life. Getting more information about sex toys and anonymity made the purchasing of sex toys easier. Partner, healthcare professionals, and friends had a major social influence on purchasing sex toys. In the future, attention should be drawn on effective communication about the different uses and sexual health benefits of sex toys.